An overview of recent laboratory measurements on dispersion and attenuation in bubbly liquids, and scattering from artificial bubble clouds - Wilson, P; Roy, R (University of Bath Press, 2005)
Effective medium (EM) models are commonly used to describe the acoustics of bubbly liquids. Regarding linear sound propagation, this approach has been successful for low void fractions and broad bubble size distributions, at frequencies away from the individual bubble resonance frequency (IBRF). For narrow size distributions at frequencies near IBRF, previously reported sound speed and attenuation measurements are not well-described by EM models. Due to high attenuation in the medium and the difficulty of independently characterizing bubble populations, experimental verification of competing models has not been achieved. An impedance tube technique was developed to overcome these difficulties and used to investigate narrow bubble size distributions at IBRF. Agreement with existing theory to a greater degree than previously reported was observed up to a void fraction of 5.4 x 10-4, within the uncertainty of the bubble population parameters. Regarding free-field scattering from clouds of freely rising bubbles, EM models have typically been found effective up to the cloud’s monopole resonance frequency. Measurements of scattering from bubble collections that had a well-defined shape were conducted. An EM scattering model was found to describe the measurements at frequencies up to three times the cloud’s monopole resonance frequency and up to 55% of the mean bubble resonance frequency.